DNA Damage Inducible Transcript 4 Gene: The Switch of the Metabolism as Potential Target in Cancer - Tirado-Hurtado, Indira; Fajardo, Williams; Pinto, Joseph A. (Frontiers in Oncology, 2018)
DNA Damage Inducible Transcript 4 (DDIT4) gene is expressed under stress situations turning off the metabolic activity triggered by the mammalian target of rapamycin (mTOR). Several in vitro and in vivo works have demonstrated the ability of DDIT4 to generate resistance to cancer therapy. The link between the metabolism suppression and aggressiveness features of cancer cells remains poorly understood since anti-mTOR agents who are part of the repertoire of drugs used for systemic treatment of cancer achieving variable results. Interestingly, the high DDIT4 expression is associated with worse outcomes compared to tumors with low DDIT4 expression, seen in a wide variety of solid and hematological tumors, which suggests the driver role of this gene and provide the basis to target it as part of a new therapeutic strategy. In this review, we highlight our current knowledge about the biology of DDIT4 and its role as a prognostic biomarker, encompassing the motives for the development of target drugs against DDIT4 as a better target than mTOR inhibitors.